(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Financial Technology (FinTech) has transformed the global financial ecosystem by enhancing financial inclusion, innovation, and digital service delivery. India has emerged as one of the world's fastest-growing FinTech markets, driven by initiatives such as the Unified Payments Interface (UPI), Aadhaar, Digital India, and the Pradhan Mantri Jan Dhan Yojana (PMJDY). Despite these advancements, disparities in financial literacy, digital literacy, cybersecurity awareness, and financial capability continue to hinder the sustainable and inclusive adoption of digital financial services. This study examines the current status of financial literacy in India and evaluates the country's readiness for FinTech development within the global digital financial ecosystem. A descriptive and comparative research design based on secondary data from internationally recognized sources, including the OECD/INFE, World Bank, International Monetary Fund (IMF), Reserve Bank of India (RBI), National Centre for Financial Education (NCFE), Bank for International Settlements (BIS), and International Telecommunication Union (ITU), is employed. The findings indicate that India has made significant progress in digital payments, financial inclusion, and digital public infrastructure, although financial capability has not advanced at the same pace as technological innovation. The study proposes an integrated conceptual framework and a multidimensional FinTech Readiness Index (FTRI) that can be used to assess national preparedness for sustainable digital financial development. The findings provide practical policy recommendations for strengthening financial literacy, digital capability, and inclusive digital finance.